AN EXPERIENCE IN TEACHING ACCOUNTANTS' REPORT WRITING BY VISUAL METHODS. - Bay, Max W. (The Accounting Review, 1953)
Abstract The undergraduate accounting student generally faces his first main experiences with the practical facts of accounting life in the course in report writing. He meets reality somewhat, of course, in such studies as auditing and taxation, but, in the main, he has been concerned primarily with theoretical concepts. He has not faced the necessity ordinarily, for example, of preparing realistic, complete, and formal communications for actual readers with vested interests. The aim of the report writing course thus becomes one of generating dear and comprehensive understanding on the part of students as to the purposes, scope, and manner of presentation of reports by independent public accountants. Personal experience has indicated that the most effective approach to realistic student comprehension of the "whole" report has been through the direct use of actual reports prepared by practicing accountants. Visual aids have provided the medium by which such reports could be handled practically in the classroom.